Wire Placement in the Sustentaculum Tali Using a 2D Projection-Based Software Application for Mobile C-Arms: Cadaveric Study - Swartman, Benedict; Schnetzke, Marc; Beisemann, Nils; Keil, Holger; Franke, Jochen; Grützner, Paul Alfred; Vetter, Sven Y. (Foot & ankle international, 2018)
Background:Indirect screw fixation of the sustentaculum tali in the lateral-medial direction can be challenging due to the complex calcaneal anatomy. A novel 2-dimensional (2D) projection-based software application detects Kirschner wires (K-wires) and visualizes their intended direction as a colored trajectory. The aim of this prospectively randomized cadaver study was to investigate whether the software would facilitate the indirect K-wire placement in the sustentaculum tali.Methods:In 20 cadaver foot specimens, K-wires were placed indirectly in the sustentaculum tali by an experienced and an inexperienced surgeon, with and without using the application. Number of placement attempts, duration of procedure, fluoroscopy time, and number of individual fluoroscopy images were recorded. Each wire?s position was analyzed in a 3-dimensional (3D) C-arm scan by an experienced blinded investigator.Results:Use of the software by the inexperienced surgeon significantly reduced the number of placement attempts from 3.2 to 1.2 (P = .006). The application also reduced operating time, from 273 s to 199 s (P = .15), and fluoroscopy time, from 41 s to 29 s (P = .15). Using the software, the experienced surgeon had a longer operating time (139 s to 183 s; P = .30), longer fluoroscopy time (5.6 s to 9.2 s; P = .17), and more individual fluoroscopy images (11.6 to 14.8; P = .30). Wire position did not show significant differences in both cases.Conclusion:During indirect K-wire placement in the sustentaculum tali, the software appeared to be a useful tool for the inexperienced surgeon. In our chosen study setting, the experienced surgeon did not benefit from the software.Clinical Relevance:Possible indications for the software would be fractures of the proximal femur, sacrum, sacroiliac instabilities, vertebral bodies, scaphoid, Lisfranc joint, talus and calcaneus.
Gesehen am 30.04.2019